First observations of fertilized eggs and preleptocephalus larvae of Rhinomuraena quaesita in the Vienna Zoo. Issue 1 (10th November 2014) - Preininger, D.; Halbauer, R.; Bartsch, V.; Weissenbacher, A.
<x xml:space="preserve">Abstract</x> For the first time worldwide, fertilized eggs of ribbon eels (Rhinomuraena quaesita) hatched into feeding preleptocephali and could be kept alive for a period of seven days in the Vienna Zoo. The study reports on husbandry, behavioral observations and dimensions of eggs and preleptocephalus larvae. Furthermore, body color variations of ribbon eels in captivity do not reflect its sex or sexual maturity. Zoo Biol. 34:85–88, 2015. © 2014 Wiley Periodicals Inc.